(untitled) - Peter J Olver (New York, 1996)
The book provides a solid introduction to those applications of Lie groups to differential equations which have proved to be useful in practice, including determination of symmetry groups, integration of ordinary differential equations, construction of group-invariant solutions to prartial differential equations, symmetries and conservation laws, generalized symmetries, and symmetry methods in Hamiltonian systems. Following an exposition of the applications, the book develops underlying theory. Many topics are presented in a novel way, with an emphasis on explicit and computations. Further examples, as well as new theoretical developments, appear in the exercises at the end of each chapter
Keywords: differential equations,lie groups